Song of Dewey Beard : Last Survivor of the Little Bighorn - Burnham, Philip (Book collections on Project MUSE., 2014)
Beard was not only a witness to two major battles against the Lakota; he also traveled with William "Buffalo Bill" Cody's Wild West show, worked as a Hollywood Indian, and witnessed the grand transformation of the Black Hills into a tourism mecca. Beard spent most of his later life fighting to reclaim his homeland and acting as "old Dewey Beard," a living relic of the "old West" for the tourists.